(untitled) (Agroindustria, Sociedad y Ambiente, 2026)
The municipality of Guamal, Meta, presents limitations in parchment coffee processing, which affects its quality, productivity, and commercial potential. Therefore, the development of this study proposes the design of a processing plant with an agrotouristic approach, aimed at improving productive efficiency and promoting sustainable rural development. An estimated installed capacity was defined according to local production, and the Systematic Layout Planning (SLP) methodology was applied to evaluate the optimal distribution of spaces and equipment. Key machines were selected such as pulpers, fermentation tanks, and solar dryers, integrating areas for waste management, water treatment, and spaces designated for visitors. The proposal complies with sanitary regulations such as Resolution 2674/2013 for Colombia, as well as international food safety standards such as HACCP and ISO 22000, and workplace safety such as 2400 of 1979, additionally considering sanitary design as part of the tourist experience. The results show an improvement in process flow, reduction of cross-contamination risks, valorization of by-products such as compost, and promotion of coffee as a cultural attraction with opportunities for agrotourism. It is concluded that the proposed plant not only strengthens the coffee value chain in the region, but also diversifies the local economy through agrotourism, articulating sustainability, food safety, education, and coffee culture.